PERTUMBUHAN EKONOMI REGIONAL DI PROVINSI JAWA BARAT - Ayu Zakya Lestari (Signifikan: Jurnal Ilmu Ekonomi, 2013)
The aim of this research is to know the effects of local government budget from number of population and human capital ratio to regional economic growth in province of West Java. This research used analysis on panel data estimation. The study results showed that all independent variables in the model can explain the variation of dependent variable, which is regional economic growth in province of West Java for 96,15%. So, throughout the research period, there were policy changes which gave the effect on regional economic growth. It can be seen from dummy variabel of regional autonomy that influences regional economic growth for significant t-value on up to 95%. Then, about local income variable which does not give effect, but the other variables; number of population gives effect and negative for 7,61% and human capital ratio which gives positive effect for 1,95% on regional economic growth.DOI: 10.15408/sjie.v2i1.2375